Quality Measurement in Neonatal Surgical Disorders: Development of Clinical Indicators - van Heurn, Ernest; de Blaauw, Ivo; Heij, Hugo; Wijnen, Marc; Wijnen, Rene; Hulscher, Jan; van der Zee, David (European Journal of Pediatric Surgery, 2015)
Objective This study aims to develop a set of quality indicators for the measurement of the quality of surgical care for neonates with surgical disorders.Methods An expert panel of the Netherlands Association of Pediatric Surgeons developed internal (clinical) indicators for neonatal surgery. This included the selection of appropriate care processes, a review of the scientific literature, consensus meetings to establish national guidelines, selection of clinical indicators with independent external evaluation, the setup of a national database, and a pilot study in one of the hospitals to evaluate the defined quality indicators in clinical practice.Results Seven neonatal surgical care processes were selected. Clinical guidelines to evaluate the care processes were established in six of seven disorders and were based on consensus agreement, which was reached in 81 to 97% of in total 220 relevant items. The expert panel selected a set of 24 indicators to estimate the quality of neonatal surgical care, of which 12 were outcome indicators and 12 process indicators.Conclusion The development of quality indicators is an important step toward monitoring and, if necessary, improving the quality of neonatal surgical care. Internal or clinical indicators guarantee that the results are only disclosed to the participating center itself and are therefore no threat to individual doctors.
Keywords: quality; pediatric surgery; indicators